2020
DOI: 10.3389/fnins.2020.575494
|View full text |Cite
|
Sign up to set email alerts
|

Measuring dlPFC Signals to Predict the Success of Merchandising Elements at the Point-of-Sale – A fNIRS Approach

Abstract: The (re-)launch of products is frequently accompanied by point-of-sale (PoS) marketing campaigns in order to foster sales. Predicting the success of these merchandising elements at the PoS on sales is of interest to research and practice, as the misinvestments that are based on the fragmented PoS literature are tremendous. Likewise, the predictive power of neuropsychological methods has been demonstrated in various research work. Nevertheless, the practical application of these neuropsychological methods is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…Most of the existing studies of advertising effects via fNIRS chose the dorsolateral prefrontal cortex (dlPFC) as the observed brain region. Some scholars have verified the reliability of fNIRS in advertising effect research by repeating previous fMRI experiments (Krampe et al, 2018;Gier et al, 2020;Meyerding and Mehlhose, 2020). Gier et al (2020) repeated Kühn et al (2016) study on the advertising effect of chocolate bars by measuring the neural activity of dlPFC, and obtained a high accuracy.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Most of the existing studies of advertising effects via fNIRS chose the dorsolateral prefrontal cortex (dlPFC) as the observed brain region. Some scholars have verified the reliability of fNIRS in advertising effect research by repeating previous fMRI experiments (Krampe et al, 2018;Gier et al, 2020;Meyerding and Mehlhose, 2020). Gier et al (2020) repeated Kühn et al (2016) study on the advertising effect of chocolate bars by measuring the neural activity of dlPFC, and obtained a high accuracy.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Building upon neuroscience research bearing on food as a motivated choice, we elaborate a conceptual framework (see Figure 1) focusing specifically on the single and compounded effect of the MS of food and the MS of marketing activities (in-store display and price) and hypothesize the impact on weekly product sales. Consumer neuroscience is recognized for its ability to represent better the impact of marketing on consumers’ decision-making and shed light on novel research variables (Chen et al , 2015; Gier et al , 2020; Krampe et al , 2018; Linzmajer et al , 2014; Lee et al , 2018; Meyerding and Mehlhose, 2020; Plassmann et al , 2012; Plassmann et al , 2015; Yoon et al , 2012). For example, research studying the dopaminergic system found that, contrary to common belief, in the presence of consumption cues such as food sampling, consumers tend to pursue further rewarding goals such as eating rather than satiating and reducing engagement in the behavior (Wadhwa et al , 2008; Yoon et al , 2012).…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%
“…Thus, in this research, we build on neuroscience theories to better understand consumer’s food purchase decision at the point-of-purchase (POP) and what drives it. Studying behavior at the POP is highly important (Gier et al , 2020). van der Lans et al (2008), while exploring the effect of brand salience, found that most of the search behavior was predicted by in-store marketing activities such as display and pricing, while a small proportion was predicted by out-of-store activities such as advertising.…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations